Pengembangan E-Penuntun Praktikum IPA Materi Klasifikasi Makhluk Hidup Berbasis Guided Inquiry untuk Siswa Kelas VII SMP: Development of E-Guide for Natural Sciences Practicum Classification of Living Creatures Based On Guided Inquiry of Class VII Middle School Students - Reza Oktaviani; Damris Muhammad; Muhaimin Muhaimin (Universitas Jambi, 2022)
Media is one of the essential components in learning to reach the highest learning outcomes. Therefore, teachers should create and utilize media in every learning process. This study aimed to develop an e-practicum manual based on guided inquiry class material for grade VII students of junior high school. The manual was developed using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected using questionnaire of media experts, material experts, and teacher and student perception questionnaires. This research was conducted at state junior high school 2 Jujuhan Bungo Regency Jambi Province. This study shows that the instructional e-practicum manual based on inquiry is considered interesting and suitable for learning.